A preliminary species‐level phylogeny of the alpine ginger Roscoea: Implications for speciation. Issue 3 (16th April 2017) - Zhao, Jian‐Li; Zhong, Jinshun; Fan, Yong‐Li; Xia, Yong‐Mei; Li, Qing‐Jun
Abstract: Speciation, the evolutionary process forming new species, is a key mode generating biodiversity on the Earth. In this study, we produced a species‐level phylogeny of Roscoea using one nuclear ribosomal and two chloroplast DNA fragments based on Bayesian inference and maximum likelihood. We then explored the possible speciation processes using the species‐level phylogeny and the heterozygous sites in the nuclear DNA. The incongruence between nuclear and chloroplast phylogenies, and several heterozygous sites in the nuclear DNA, suggested that R. auriculata might have a hybrid origin with R. purpurea and R. alpina being two possible parental progenitors; however, one alternative possibility through incomplete lineage sorting cannot be ruled out. In addition, R. kunmingensis likely originated from R. tibetica Batalin through the process of "budding speciation". These results provided a valuable framework to draw testable hypotheses for future in‐depth comparative studies to further our understanding of the underpinning speciation and adaptation mechanisms that contribute to ultrahigh biodiversity in the Himalayas and the Hengduan Mountains.